PbGP43 Genotyping Using Paraffin-Embedded Biopsies of Human Paracoccidioidomycosis Reveals a Genetically Distinct Lineage in the Paracoccidioides brasiliensis Complex - Ricci, Giannina; Campanini, Emeline Boni; Nishikaku, Angela Satie; Puccia, Rosana; Marques, Mariângela [UNESP]; Bialek, Ralf; Rodrigues, Anderson Messias; Batista, Wagner Luiz (Springer Nature, 2021)
Paracoccidioidomycosis (PCM) is a systemic mycosis caused by a group of cryptic species embedded in the Paracoccidioides brasiliensis complex and Paracoccidioides lutzii. Four species were recently inferred to belong to the P. brasiliensis complex, but the high genetic diversity found in both human and environmental samples have suggested that the number of lineages may be higher. This study aimed to assess the 43-kilodalton glycoprotein genotypes (PbGP43) in paraffin-embedded samples from PCM patients to infer the phylogenetic lineages of the P. brasiliensis complex responsible for causing the infection. Formalin-fixed, paraffin-embedded (FFPE) tissue samples from patients with histopathological diagnosis of PCM were analyzed. DNAs were extracted and amplified for a region of the second exon of the PbGP43 gene. Products were sequenced and aligned with other PbGP43 sequences available. A haplotype network and the phylogenetic relationships among sequences were inferred. Amino acid substitutions were investigated regarding the potential to modify physicochemical properties in the proteins. Six phylogenetic lineages were identified as belonging to the P. brasiliensis complex. Two lineages did not group with any of the four recognized species of the complex, and, interestingly, one of them comprised only FFPE samples. A coinfection involving two lineages was found. Five parsimony-informative sites were identified and three of them showed radical non-synonymous substitutions with the potential to promote changes in the protein. This study expands the knowledge regarding the genetic diversity existing in the P. brasiliensis complex and shows the potential of FFPE samples in species identification and in detecting coinfections.
Keywords: Formalin-fixed paraffin-embedded (FFPE) biopsies; Molecular diagnosis; Paracoccidioides brasiliensis complex; PbGP43 genotyping; PCR